2014
DOI: 10.1123/jpah.2012-0137
|View full text |Cite
|
Sign up to set email alerts
|

Motor Coordination, Activity, and Fitness at 6 Years of Age Relative to Activity and Fitness at 10 Years of Age

Abstract: Results highlight the need to consider not only PA, but also PF and GMC in health promotion through the primary school years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 29 publications
1
26
0
Order By: Relevance
“…However, the strength of associations across developmental time remains unclear . Over time, there is some evidence which shows that children's TPA levels decrease with age and that this condition may affect their GMC levels . Similarly, Lopes, Rodrigues, Maia, and Malina found that children's GMC influences their PA levels from 6 till 10 years of age, that is, less coordinated children decreased their PA with increasing age, whereas the opposite occurred with more coordinated children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the strength of associations across developmental time remains unclear . Over time, there is some evidence which shows that children's TPA levels decrease with age and that this condition may affect their GMC levels . Similarly, Lopes, Rodrigues, Maia, and Malina found that children's GMC influences their PA levels from 6 till 10 years of age, that is, less coordinated children decreased their PA with increasing age, whereas the opposite occurred with more coordinated children.…”
Section: Discussionmentioning
confidence: 99%
“…Children change their body size and composition as well as their body proportions and overall shape as they grow. Similarly, their motor performance (MP) and gross motor coordination (GMC) also increases with age . Whilst a number of correlates have potential to influence GMC, a recent systematic review established that child‐level variables such as age, sex (boys), physical activity, fitness, and weight status are all important .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we need more longitudinal research that examines the development of motor competence over time and its relationship with other health-related outcomes. For instance, de Souza et al (2014) compared motor competence, physical activity and physical fitness of children at 6 years of age relative to their physical fitness and physical activity levels at 10 years. The authors found that children who were both fit and active at 10 years of age had a more favorable activity and fitness profile at 6 years and they were also more competent at 6 years compared to their unfit and sedentary peers.…”
Section: Introductionmentioning
confidence: 99%
“…Given the increasing prevalence of overweight/obesity and the reduction of habitual physical activity early in age (World Health Organization, 2000), the investigation of prepubertal children in respect of physical fitness and anthropometry and body composition is especially important for effective intervention such as reduced energy intake, increased physical activity and decreased sedentary behavior (Martin et al, 2018). In fact, it has been found that children who were fit and active at 10 years of age have had better physical fitness at 6 years of age vs. peers who were less fit and sedentary (De Souza et al, 2014). Also, the level of physical fitness has been positively associated with cognitive function and academic achievement in children (Donnelly et al, 2016) as well as higher risk of developing cardiovascular diseases, mental disorders, and skeletal problem later in life (Ruiz et al, 2009).…”
Section: Introductionmentioning
confidence: 99%